Pengaruh Kinerja Keuangan, Ukuran Perusahaan dan Manajemen Laba Terhadap Return Saham dengan Kebijakan Dividen sebagai Variabel Moderasi - Muhamad Nazhif Hawari; Zuwesty Eka Putri (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
This research aims to test influence of financial performance, company size and profit management on return of shares with dividend policy as moderation variable. This research was conducted in a manufacturing company registered in Indonesia Sharia stock index (ISSI) period 2016-2018. The sampling method in this study uses purposive sampling. The number of samples on this study was as many as 20 companies. The financial performance of the study is calculated by a debt to equity ratio. Hypothesis testing in this study used multiple regression methods and moderated regression analysis. The result of this research show the financial performance and company size has no effect on the stock return and earning management affects the stock return. Dividend policy is not able to moderate the influence of financial performance, company size and profit management on return of shares